Problem of Abbreviations in Arabic Manuscripts - Alić, Salih H. (Prilozi za orijentalnu filologiju, 2017)
Various abbreviations and numerous signs, wh1ch can be found in all Arabic manuscripts present a special difficulty for the correct reading and full utilization of an Arabic manuscript. The present author wants to emphasize that the problem of those abbreviations has not so far been given special attention. Then the similarity between the Greek cultural tradition ·in writing, in which abbreviations are also found, and the early Arabic papers has been surveyed. Knowledge of the frequently used abbreviations, especially in the manuscripts of certain sciences and professions is a necessary prerequisite for the reading of the manuscripts. It is obvious, that in case that those abbreviations are misread or remain marked as unclear, the text itself will not he clear. The present author also points out that some recognized scholars in Arabic have misread those abbreviations, and offers a number of examples. Those very mistakes make one wonder why hardly any attention has so far been paid to the problem of those abbreviations in Arabic. Finally, certain kinds of abbreviations in Arabic manuscripts have been given a list of the most frequent abbreviations, which was found in a manuscript of the work by al-Wikaya from the 16th century, in which there were 27 abbreviations, has been given.